IMPLEMENTASI PEMBELAJARAN PEMASARAN BERBASIS KARAKTER DI KELAS XII SMKN 10 CAWANG - Dharmawati, Desak Made; Sumarsid, - (E-Journal Widya Ekonomika, 2020)
Character building believes the existence of absolute morale, i.e., comprehension about which one is proper and right. Character building instill habituation of the good practice so that student know about which is right or wrong (cognitive domain) and feel the good value. The objective of this research is understanding student's change in daily behaviour, including communication attitude or maturity, and identifying the local culture and the meaning of the values ​​of thei nation's character in the local community. Marketing learning processes that have the values ​​of national character. The research method uses descriptive qualitative model, the results of the data instrument interview results in the field, there is a change in character, it can be seen from the daily attitude of students to be honest, disciplined, responsible, caring, collaborative, tolerant, peaceful, polite, responsive and pro-active and showing attitude as part of the solution to various environmental problems.